2009
DOI: 10.1159/000200443
|View full text |Cite
|
Sign up to set email alerts
|

Patients at High Risk of Cerebrovascular Disease: The REACH Study

Abstract: Cerebrovascular disease is one of the leading causes of morbidity and mortality in developed countries. The identification of at-risk individuals is a high priority so that efficacious preventive measures can be implemented. Subjects with the highest risk of cerebrovascular diseases are those who already have had a stroke or a transient ischemic attack, and those with vascular disease in other territories, either in coronary or peripheral arteries. Other subjects at risk are those with cardiac disease, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Therefore, the damage of CS not only limits to lung tissue but also vascular system. CS is a known risk factor not only for peripheral cardiovascular inflammation-related diseases [2,3] but also for cerebrovascular diseases, such as stroke [4]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the damage of CS not only limits to lung tissue but also vascular system. CS is a known risk factor not only for peripheral cardiovascular inflammation-related diseases [2,3] but also for cerebrovascular diseases, such as stroke [4]. …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, CS or chemicals present in CS have been shown to induce HO-1 expression in various cell types [7-10] including cerebral endothelial cells [11]. Therefore, PPCSE-induced HO-1 expression in cerebral vessels might be an important factor for brain injury in hemorrhagic stroke which incident rate has been correlated with cigarette smoking previously [4]. …”
Section: Introductionmentioning
confidence: 99%
“…This is of clinical relevance as the expression of ApoE and LDL receptors differs in young adult versus old rats following cerebral ischemia [47]. Atherosclerosis is an important risk factor in patients with ischemia [48]. Therefore, consideration of this pathology in animal stroke models is crucial.…”
Section: Atherosclerosismentioning
confidence: 99%
“…The international Reduction of Atherothrombosis for Continued Health (REACH) registry of 67,888 patients with symptomatic atherothrombotic disease showed that 41% of patients with stroke/TIA (18,843 patients with predominantly non-cardiogenic ischaemic stroke) also had disease in at least one additional vascular territory [5,10,11]. Patients with documented polyVD have more than double the risk of a major event or hospitalisation at 1 year compared with patients in whom only the cerebral territory is involved (fig.…”
Section: Stroke Patients With Polyvd: a High-risk Populationmentioning
confidence: 99%